Effects of concentration and frequency of paclobutrazol application on growth, yield and quality of watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai] - Abdul Raza, Mutmain (2022)
Watermelon (Citrullus lanatus) excessively grows and has an abundantly branching habit, resulting in a requirement of continual pruning to control vegetative growth and trigger reproductive development. Paclobutrazol (PBZ) is a plant growth regulator commonly used in agriculture to control plant height and increase yields. Previous studies have shown that PBZ can significantly reduce plant height. However, the effect of PBZ on the growth and yield of watermelons grown under a greenhouse is unknown. Thus, the objectives of this study were to investigate the effects of PBZ different concentration, watermelon varieties, and frequency of PBZ application on growth performance, yield production, and quality of watermelon grown under greenhouse conditions. In the first experiment, the effects of five concentrations (0, 250, 500, 750, and 1000 mg/L) of PBZ were applied as a foliar spray on three varieties of watermelon: Mellow oblong (GE344), Red Delight (GE341), and Oval Yellow (SSH348) and their growth and yield were evaluated. The experiment was arranged in a factorial Randomized Complete Block Design (RCBD) with three replications. Among the PBZ treatments, the reduction in plant height for 250 mg/L was almost 14.26% compared to the non-treated plants, while watermelon applied with 1,000 mg/L PBZ showed extremely lowest plant height. This study shows that the variety GE344 Mellow oblong was better, and produced significantly the highest relative chlorophyll content, TSS%, fruit weight, number of the female flower, and root volume compared to other treatments. The highest relative chlorophyll content, percentage of TSS, fruit diameter, and root fresh and dry weights, root diameter was found in the application of 250 mg/L PBZ as compared to other PBZ concentrations. The application of 250 mg/L of PBZ increased relative chlorophyll content, number of the female flower, root fresh weight, root dry weight, root diameter, and fruit diameter rate by 61.12%, 71.63%, 51.49%, 42.12%, 48.38%, 57.20%, and 18.83%, respectively, compared to the non-treated plants. In the second experiment, the treatment involved the best variety from Experiment 1 (Mellow oblong), and three frequencies of PBZ application: T0 = control (without PBZ application), T1 = single application of 250 mg/L applied at 15 DAT, and T2 = 125 mg/L of PBZ applied twice at 15 and 30 DAT were used. Watermelon plant received T1 treatment resulted the highest lycopene content compared to T2 and T0. Watermelon plant treated with T1 obtained the highest chlorophyll a, relative chlorophyll content, lycopene content, total phenolic content and increased by 30.22%, 39.14%, 35.15%, and 119.58%, and significantly decreased by 21.48% of plant height, respectively than control. T2 treatment decreased leaf area, leaf dry weight, and fruit weight by 14%, 15%, and 38.32%, respectively, compared to the non-treated plants. In conclusion, the application of T1 (250 mg/L of PBZ and single frequency) as a foliar spray controls growth, improved yield and quality as well as the physiological process of watermelon crop.